Oral cleft prevention program (OCPP) - Wehby George L; Goco Norman; Moretti-Ferreira Danilo; Felix Temis; Richieri-Costa Antonio; Padovani Carla; Queiros Fernanda; Guimaraes Camilla Vila; Pereira Rui; Litavecz Steve; Hartwell Tyler; Chakraborty Hrishikesh; et al. (BMC, 2012)
Abstract Background Oral clefts are one of the most common birth defects with significant medical, psychosocial, and economic ramifications. Oral clefts have a complex etiology with genetic and environmental risk factors. There are suggestive results for decreased risks of cleft occurrence and recurrence with folic acid supplements taken at preconception and during pregnancy with a stronger evidence for higher than lower doses in preventing recurrence. Yet previous studies have suffered from considerable design limitations particularly non-randomization into treatment. There is also well-documented effectiveness for folic acid in preventing neural tube defect occurrence at 0.4 mg and recurrence with 4 mg. Given the substantial burden of clefting on the individual and the family and the supportive data for the effectiveness of folic acid supplementation as well as its low cost, a randomized clinical trial of the effectiveness of high versus low dose folic acid for prevention of cleft recurrence is warranted. Methods/design This study will assess the effect of 4 mg and 0.4 mg doses of folic acid, taken on a daily basis during preconception and up to 3 months of pregnancy by women who are at risk of having a child with nonsyndromic cleft lip with/without palate (NSCL/P), on the recurrence of NSCL/P. The total sample will include about 6,000 women (that either have NSCL/P or that have at least one child with NSCL/P) randomly assigned to the 4 mg and the 0.4 mg folic acid study groups. The study will also compare the recurrence rates of NSCL/P in the total sample of subjects, as well as the two study groups (4mg, 0.4 mg) to that of a historical control group. The study has been approved by IRBs (ethics committees) of all involved sites. Results will be disseminated through publications and presentations at scientific meetings. Discussion The costs related to oral clefts are high, including long term psychological and socio-economic effects. This study provides an opportunity for huge savings in not only money but the overall quality of life. This may help establish more specific clinical guidelines for oral cleft prevention so that the intervention can be better tailored for at-risk women. ClinicalTrials.gov Identifier NCT00397917